Development of antibacterial magnetic clay-based nanocomposites for water treatment - Horue, Manuel (2023)
Organoclays with antibacterial activity were prepared using an Argentinean montmorillonite (Mt), and hexadecyl trimethyl ammonium or benzalkonium chloride at different concentrations (50 %, 100 %, and 150 %) with respect to the Mt cation exchange capacity (CEC). Afterward, Fe oxides were grown onto the attained organoclays. The materials were characterized and tested against E. faecalis, E. coli, and S. typhimurium. The interlayer space of Mt after surfactant incorporation was, for all organoclays, higher than the determined for natural Mt, indicating the molecules incorporation at this site. Besides, DTGA analysis allows determining the surfactant amount on both, external and internal surfaces of the organoclays and magnetic organoclays. As a general result, the higher the initial concentration of surfactant, higher the actual load on the clay and the surfactant in the external surface, which is the principal responsible of the biocide capacity of the materials. The principal formed Fe oxide was magnetite, although the presence of maghemite cannot be discharged, and all magnetic composites presented a high enough saturation magnetization value for manipulating the materials by means of an external magnetic field. The higher size of the benzalkonium chloride molecule seems to play a relevant role in Fe oxides formation. Inhibition experiments showed high antibacterial activity against E. faecalis, E. coli, and S. typhimurium. The synthesized nanocomposites loaded with 150 % CEC of hexadecyl trimethyl ammonium were the most effective, according to the surfactant concentration at the external surface. Subsequently, more rigorous trials employing those samples were made on a larger scale and a viable plate count method was selected to determine bactericidal potential with higher precision. The magnetic materials had similar antimicrobial effectivity compared with non-magnetic ones, indicating that Fe oxides can be nucleated to impart magnetic response but without affecting the biocide properties. The organoclays showed higher antibacterial activity against E. coli compared with the other used bacteria. In addition, the agar disk-diffusion method revealed that antimicrobial agents did not release from clays, relevant for quality of the treated waters.